The study of internal marketing in the hotel industry of Singapore. - Chan, Vee Mun. (2008)
Internal marketing is increasingly recognised as an important activity in developing a customer-focused organisation. It is now becoming evident that in most organisations - especially the service delivering businesses like hotels - that a strong internal marketing program needs to be in place before excellent external service quality can be provided to customers. Our study investigates what hotel employees want in an internal marketing program and the current status of such programs.